(untitled) (قضايا سياسية, 2024)
This study seeks to address the phenomenon of asylum in developing countries in the Middle East region by applying it to Sudanese refugees in the Egyptian state. The paper seeks not only to study the policies of the receiving countries towards refugees, but also to study the interaction between those policies and the practices of other actors associated with the management of refugee affairs and the practices of the refugees themselves as actors, and the impact of this on rereading the citizen-nation-territory axis on which the concept of sovereignty is based. In this context; Many researchers from various fields such as political science, anthropology, urban studies, and others argue to present the refugee as an actor with ability and action who can change and face the challenges imposed on him on the one hand and present alternative political perceptions collectively or individually, which are in fact changes that transcend political and cultural boundaries. and the social nature of the nation-state. Therefore, the paper discusses that in the face of the official policies of exclusion imposed by the Egyptian state on the spaces of Sudanese refugees and dealing with them from a security perspective only, the refugees do not stand as a passive actor, but rather try to produce means and practices of resistance in order to secure their minimum rights, and in the midst of that interaction between the state’s policies towards... Refugees, the practices of refugees, and other actors involved in managing their affairs produce other alternative patterns of sovereignty that challenge the sovereignty of the receiving state, and thus generate the effectiveness of refugees to confront the state of exception imposed on them by the state and the impact of this on the concept of state sovereignty.